Revit 2020: Essential Training for MEP (Imperial). - Wing, Eric (linkedin.com, 2019)
Learn the basics of MEP design in Revit 2020. This course covers mechanical, electrical, plumbing, and fire protection design, using examples in imperial units (inches and feet).